The implementation of learning methodology based on problems: experience report. - Fonseca AS; Pires PS; Miranda SM (Nursing Sao Paulo, 2007)
Our century professionals need to be up to dated, search for new information, be critical and reflexive. Teaching methods that limit the know-ledge in the professor image showed to be ineffective to educate futures nurses. That's an experience report that aims to describe the process of implementation of Anhembi Morumbi Nursing Graduation Course pedagogical project, by using the problem-based learning method. The model is being developed in a private university, in nursing graduation course and, for doing so, it was necessary that the students and professors changed their behavior and attitudes. Such experience has provided improvement to everyone involved and new studies will be done so as to analyze the perception of this process in the student and professor's view.